2002
DOI: 10.1177/074873002129002582
|View full text |Cite
|
Sign up to set email alerts
|

Extraocular Light Exposure Does Not Phase Shift Saliva Melatonin Rhythms in Sleeping Subjects

Abstract: Preliminary work in humans suggests that extraocular light can shift circadian phase. If confirmed, extraocular light may be of therapeutic benefit in the treatment of circadian-related sleep disorders with the advantage over ocular exposure that it can be administered while subjects are asleep. In sleeping subjects, however, the effect of extraocular light exposure on circadian phase has yet to be fully tested. Likewise, there is limited data on the acute effects of extraocular light on sleep and body tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Whether related or not with plasma melatonin, SMC shows in the present work a clear rhythmicity, that may even represent changes occurring at tissue level. An ELISA kit used in the present work yielded SMC values very similar to those reported by others ( Lushington et al, 2002 ; Verheggen et al, 2012 ).…”
Section: Discussionsupporting
confidence: 89%
“…Whether related or not with plasma melatonin, SMC shows in the present work a clear rhythmicity, that may even represent changes occurring at tissue level. An ELISA kit used in the present work yielded SMC values very similar to those reported by others ( Lushington et al, 2002 ; Verheggen et al, 2012 ).…”
Section: Discussionsupporting
confidence: 89%
“…14 -16 With the use of 2-deoxyglucose, day-night oscillations in SCN metabolic activity have been detected in squirrel monkeys and baboons. [17][18][19] Lesion studies performed in the early 1980s suggested the presence of a circadian pacemaker outside the SCN in monkeys. 20 However, analysis of these reports revealed that either the completeness of the lesions was not verified or monkeys were not studied in constant conditions.…”
Section: The Primate Circadian Timing Systemmentioning
confidence: 99%
“…[27][28][29] Furthermore, other investigators have failed to reproduce phase-shifting effects of cutaneous light exposure. 17 Outputs of the primate circadian system have been widely characterized in human clinical studies. Many day-night rhythms have been documented.…”
Section: The Primate Circadian Timing Systemmentioning
confidence: 99%
“…However, using probes for melatonin receptors and SCN peptides, the human SCN can be identified [19][20][21] . Using DG, day-night oscillations in SCN metabolic activity have been detected in squirrel monkeys and baboons [22][23][24] .…”
Section: The Primate Circadian Systemmentioning
confidence: 99%
“…Although it was suggested that cutaneous light exposure can influence circadian function 31 , there is little support for the notion that there is extraretinal photoreception in mammals [32][33][34] . Furthermore, other investigators have failed to reproduce phase shifting effects of cutaneous light exposure 22 .…”
Section: The Primate Circadian Systemmentioning
confidence: 99%